From Acting to Action: Delphine Seyrig, Les Insoumuses, and Feminist Video in 1970s France (Konturen, 2022)
Mostly known as one of the leading actresses in 1960s-1970s French cinema, Delphine Seyrig was also a media and a feminist activist working collaboratively within the framework of the women’s liberation movement. This article proposes to tackle Seyrig’s involvement in feminist video production the 1970s and explores the continuum she inhabited, from the auteur cinema in which she was actress and muse, to the disobedient practices in which she was video maker, actress and activist. Seyrig’s meditation on her work as an actress, as well as on the patriarchal structures sustaining the film industry, strongly resonates with recent debates prompted by the #metoo movement.